l-Arginine alleviates heat stress-induced intestinal epithelial barrier damage by promoting expression of tight junction proteins via the AMPK pathway - Xia, Zhaofei; Huang, Liqing; Yin, Peng; Liu, Fenghua; Liu, Yanhan; Zhang, Zhenbiao; Lin, Jiabao; Zou, Wenshu; Li, Chunxiao (Molecular biology reports, 2019)
Heat stress (HS) and secondary restricted blood flow to the intestines cause dysfunction of the intestinal epithelial barrier. Tight junctions (TJs) are essential to maintain intestinal integrity. l -Arginine has beneficial effects on gut functions. However, the underlying mechanisms remain largely unknown. This study tested the hypothesis that l -arginine regulates the TJ network by activating AMP-activated protein kinase (AMPK) signaling, which in turn improves intestinal barrier functions under HS. IEC-6 cells and rat small intestines were used as experiment models of heat stress. AICAR and dorsomorphin were used to activate and inhibit the AMPK pathway, respectively. Cell proliferation, apoptosis, differential gene expression and KEGG pathway analysis, intestinal paracellular permeability, intestinal morphology, and expression of HSP and TJ proteins, and p-AMPK were determined. l -Arginine promoted cell proliferation and reduced apoptosis after heat exposure at an optimal concentration of 5 mmol. Transcriptome sequencing analysis revealed that differentially expressed genes associated with the HSP family and TJs were elevated by l -arginine. According to KEGG pathway analysis, l -arginine activated the AMPK signaling pathway. In vivo, intestinal damage resulted in obvious morphological changes as well as apoptosis with TUNEL and caspase-3 staining under HS and dorsomorphin treatments. Furthermore, HS and dorsomorphin increased the serum D-lactate concentration, diamine oxidase activity, and mRNA expression level of MLCK ( P < 0.05). In contrast, l -arginine and AICAR treatments reduced intestinal injury, maintained intestinal permeability, and increased the villus/crypt ratio under hyperthermia. l -Arginine had the same effect as AICAR both in vitro and in vivo, namely increasing p-AMPK protein expression. l -Arginine and AICAR also upregulated the mRNA expression level of HSP70 and HSP90, and downregulated mRNA expression of MLCK ( P < 0.05). The protein expression levels of TJ proteins ZO-1 and claudin-1 were suppressed by heat stroke and dorsomorphin, but enhanced by l -arginine and AICAR. Our findings indicate that activation of AMPK signaling by l -arginine is associated with improved intestinal mucosal barrier functions by enhancing the expression of TJs in rat small intestines and IEC-6 cells during HS.